2005
DOI: 10.1517/14622416.6.4.399
|View full text |Cite
|
Sign up to set email alerts
|

β 2 -Adrenergic Receptor Polymorphisms and Response to Salbutamol Among Indian Asthmatics *

Abstract: This study suggests that the SNP at nucleotide position 46 has particular relevance to pharmacogenetics in the Indian population studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Similar results have been reported in multiple other populations, suggesting they are correct [49,50,52]. However, replication attempted in the Indian population reported exactly the opposite effect of these genotypes [53], and others have found either no difference between Gly16 and Arg16 receptor variants [44] or decrease in response in mild asthmatics carrying the homozygous Arg16 genotype that [54].…”
Section: And Corticosteroidssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results have been reported in multiple other populations, suggesting they are correct [49,50,52]. However, replication attempted in the Indian population reported exactly the opposite effect of these genotypes [53], and others have found either no difference between Gly16 and Arg16 receptor variants [44] or decrease in response in mild asthmatics carrying the homozygous Arg16 genotype that [54].…”
Section: And Corticosteroidssupporting
confidence: 84%
“…Others have not found such a striking difference in studies including both pediatric [53] and adult patients [37]. In a study addressing …”
Section: And Corticosteroidsmentioning
confidence: 95%
“…Haplotype associations were noted for the bronchoprotection, but not for the acute bronchodilator effect. Several other studies have shown associations with ␤ 2 AR 5Ј-flanking SNPs or haplotypes and agonist (or related) phenotypes (18)(19)(20). Of note, in these latter studies in particular, haplotypes were often "reduced" to encompass one or two individual SNPs in the coding region based on linkage disequilibrium and the limited number of patients with certain haplotypes.…”
Section: Table 2 Results Of Electrophoretic Mobility Shift Assay Stumentioning
confidence: 99%
“…The intronless ␤ 2 AR gene has at least 20 polymorphisms in the promoter, 5ЈUTR, and 5Ј-leader cistron (collectively termed here as the "5Ј-flanking region"), which have allele frequencies of 0.05 (5%) in U.S. individuals of European or African descent (11,14). Clinical studies (11,(15)(16)(17)(18)(19)(20) using haplotypes derived from various sets of 5Ј-flanking and coding single-nucleotide polymorphisms (SNPs) have revealed several, and sometimes discordant, findings (see Discussion). To begin to understand the basis for in vitro and clinical phenotypes, in the current study, we have examined each polymorphism within the context of the binding of transcription factors derived from both human airway smooth muscle and airway epithelial cells.…”
mentioning
confidence: 99%
“…38 Additionally, in an Indian population, response to salbutamol treatment of asthmatic patients depends on polymorphisms of the beta 2 adrenergic receptor. 39 …”
Section: Antihypertensive Drugs and Receptorsmentioning
confidence: 99%